The Study of Mechanical Properties of Poly(lactic) Acid Pla-based 3d Printed Filament under Temperature and Environmental Conditions - Ahmad Adnan Bin Abu Bakar; Muhammad Zulhilmi Bin Zainuddin; Ahmad Nurhelmy Bin Adam; Ikhwan Syafiq Bin Mohd Noor; Nizam Bin Tamchek; Muhammad Syafiq Bin Alauddin; Mohd Ifwat Bin Mohd Ghazali (Elsevier, 2024)
Indexed by WOS/SCOPUS/ERA